Rock climbing injury prevention warm-up - Vagy, J. (The Prehab Guys, 2020)
Most climbers know better than to just jump on their project cold. However, a lack of knowledge and guidance may lead novice climbers to miss out on a proper rock climbing injury prevention warm-up! A thorough warm-up increases blood flow, muscle flexibility, and body control. In this article, you`ll gain access to the best rock climbing injury prevention warm-up from the climbing doctor himself!